The Unusual Photochromic and Hydrochromic Switching Behavior of Cellulose‐Embedded 1, 8‐Naphthalimide‐Viologen Derivatives in the Solid‐State. Issue 36 (19th May 2021) - Sun, Zhimin; Ni, Yanhai; Prakasam, Thirumurugan; Liu, Wenqi; Wu, Huang; Zhang, Zhao; Di, Haiting; Baldridge, Kim K.; Trabolsi, Ali; Olson, Mark A.
Abstract: Stimuli‐responsive chromic materials such as photochromics, hydrochromics, thermochromics, and electrochromics have a long history of capturing the attention of scientists due to their potential industrial applications and novelty in popular culture. However, hybrid chromic materials that combine two or more stimuli‐triggered color changing properties are not so well known. Herein, we report a design strategy that has led to a series of emissive 1, 8‐naphthalimide‐viologen dyads which exhibit unusual dual photochromic and hydrochromic switching behavior in the solid‐state when embedded in a cellulose matrix. This behavior manifests as reversible solid state fluorescence hydrochromism upon changes in atmospheric relative humidity (RH), and reversible solid state photochromism upon generation of a cellulose‐stabilized viologen radical cation. In this design strategy, the bipyridinium unit serves as both a water‐sensitive receptor for the hydrochromic fluorophore‐receptor system, and a photochromic group, capable of eliciting its own visible colorimetric response, generating a fluorescence quenching radical cation with prolonged exposure to ultraviolet (UV) light. These dyes can be inkjet‐printed onto cellulose paper or drop‐cast as cellulose powder‐based films and can be unidirectionally cycled between three different states which can be characteristically visualized under UV light or visible light. The material's photochromism, hydrochromism, and underlying mechanism of action was investigated using computational analysis, dynamic vapor sorption/desorption isotherms, electron paramagnetic resonance spectroscopy, and variable humidity UV‐Vis adsorption and fluorescence spectroscopies. Abstract : Water and Light Triggered Chromic Switching ! A series of emissive 1, 8‐naphthalimide‐viologen dyads were found to exhibit unusual dual photochromic and hydrochromic switching behavior in the solid phase when embedded in a cellulose matrix. Relying on humidity‐sensitive solid state fluorescence hydrochromism and photoreduction processes, the dyads could be cycled unidirectionally between three distinct chromic states. Mechanistic investigations provided new insights into the role of cellulose‐stabilized viologen radical cations in the process.